Folk Medicine in Phra Nakhon Si Ayutthaya Province: Health Wisdom and Development to a Health and Cultural Tourism Model - Kasempholkoon, Aphilak (Mekong-Salween Civilization Studies Journal, 2020)
Thailand is regarded as the leader of health tourism in Southeast Asia, both modern and folk medicines. For this reason, folk medicine has received greater interests and has been revitalized for tourism purposes. However, conventional management may be ineffective in supporting health and cultural tourism in Thailand completely. This article was conducted in order to explore the importance and current stage of health and cultural tourism in Thailand, study local wisdoms concerning cultural heritage of folk medicine in Phra Nakhon Si Ayutthaya Province, and analyze and explore possible developments of folk medicine that could help to promote the province as a health and cultural tourism destination. Data were collected from 25 pre-determined informants in Phra Nakhon Si Ayutthaya Province. Results revealed that health tourism in Thailand consisted of medical tourism and wellness tourism which could be classified into 7 types of treatment including: 1. compressing massage, 2. fire foot pedal massage, 3. wooden foot massage, 4. Thai massage, 5. lying by the fire after childbirth, 6. spraying the medicine/ sweeping medicine/blowing mantra, and 7. the treatment according to each individual’s body condition. Apart from using herbal treatments and medical procedures, moral supports, both Buddhism and Islamic beliefs, were also used. Regarding the guidelines for the development of folk medicine in Phra Nakhon Si Ayutthaya Province, it was revealed that the services and products related to folk medicine received insufficient promotional supports. Furthermore, a coordinated information center for health and cultural tourism for other localities and foreign travelers remained absent. Besides, development of health and cultural tourism should focus on constructing an online database to create a network cultural tourism which would allow tourists to plan their trips in advance. In addition, wider distribution channels for folk medicine products should also be created in order to distribute these products to consumers.